Current status of knowledge about end-user preferences for boiled potato in Uganda – A food science, gender and demand perspective - Kisakye, S.; Tinyiro, S.E.; Mayanja, S.; Naziri, D. (International Potato Center, 2020)
This report synthetizes the current state of knowledge about preferred characteristics for boiled potato among the different value chain actors; demand and profitability for the product in urban and peri-urban areas; and the agronomic practices and gender norms surrounding the potato product in Uganda. A literature review as well as key informant interviews were conducted to obtain information. From the findings, preferred physicochemical characteristics of raw and boiled potato are centered on appearance, color, size, texture and dry matter content. This can inform a more demand-oriented breeding by CIP and national partners. Potato is important for food and income generation for both men and women value chain actors, hence new potato varieties have been adopted in the different regions of Uganda. Across the value chain, the potato product has been found to be highly profitable.